2004
DOI: 10.1038/sj.ijir.3901196
|View full text |Cite
|
Sign up to set email alerts
|

Effect of life-style factors on incidence of erectile dysfunction

Abstract: We estimated the incidence of erectile dysfunction (ED) in a population-based sample during 5-y follow-up and determined how the rate was affected by sociodemographic and life-style factors. The target population comprised all men aged 50, 60 or 70 y residing in the city of Tampere or 11 surrounding municipalities in Finland at the start of follow-up. A questionnaire was mailed to 3143 men in 1994 and to 2864 in 1999. The follow-up sample consisted of 1442 men who responded to both baseline and follow-up quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
2
10

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 34 publications
(58 reference statements)
1
46
2
10
Order By: Relevance
“…A dosis más elevadas y/o en periodos de tiempo más prolongados, los efectos de las drogas son devastadores, afectando tanto a los aspectos físiológicos del ciclo sexual (Argiolas, 1999;Crenshaw y Goldberg, 1996;Cocores, Miller, Pottash y Gold, 1988;Johnson, Phelps y Cottler, 2004), como a los aspectos psicológi-cos de la sexualidad (Aguilar et al, 2008;Ávila Escribano, Pérez Madruga, Ólazabal Ulacia y López Fidalgo, 2004;La Pera et al, 2003;Lévy y Garnier, 2006;Peugh y Belenko, 2001;Rosen, 1991;Smith, 2007). Asimismo, es importante destacar la influencia que el tabaco tiene sobre la respuesta sexual humana, tanto a corto, como a largo plazo (Gades et al, 2005;Shiri et al, 2004).…”
Section: Introductionunclassified
“…A dosis más elevadas y/o en periodos de tiempo más prolongados, los efectos de las drogas son devastadores, afectando tanto a los aspectos físiológicos del ciclo sexual (Argiolas, 1999;Crenshaw y Goldberg, 1996;Cocores, Miller, Pottash y Gold, 1988;Johnson, Phelps y Cottler, 2004), como a los aspectos psicológi-cos de la sexualidad (Aguilar et al, 2008;Ávila Escribano, Pérez Madruga, Ólazabal Ulacia y López Fidalgo, 2004;La Pera et al, 2003;Lévy y Garnier, 2006;Peugh y Belenko, 2001;Rosen, 1991;Smith, 2007). Asimismo, es importante destacar la influencia que el tabaco tiene sobre la respuesta sexual humana, tanto a corto, como a largo plazo (Gades et al, 2005;Shiri et al, 2004).…”
Section: Introductionunclassified
“…4,8 ED is the most common sexual dysfunction among men aged above 40 years and its prevalence is between 41.7 and 53.4% in different countries of America. 2,3,5,9,10 In Europe, a study of 2869 Austrian men found a prevalence of 32.2% (all degrees of severity). 11 In Finland in 3787 men aged 50-75 years, the prevalence of ED was 76.5%.…”
Section: Discussionmentioning
confidence: 99%
“…2 Documented behavioral correlates of ED include lifestyle issues such as cigarette smoking, obesity, stress, alcohol and drug abuse. 2,5 ED can have negative effects on male social and psychological well-being, mood state, interpersonal relationships and quality of life, leading to the lack of emotional and physical intimacy, lower satisfaction with their relationship and sexual life. 6,7 The heavy educational, marketing and media awareness campaigns after the market launch of phosphodiesterase type 5 inhibitors (PDE5I): sildenafil and vardenafil or the first representative of second-generation PDE5I (tadalafil) were expected to change the perception of ED among both patients and physicians.…”
Section: Introductionmentioning
confidence: 99%
“…The association between drinking and ED was also found to be inconsistent in prospective studies. 5,13,23 One of the possible explanations for the unclear effect of drinking on ED may be due to the J-shaped relationship. For example, if there are equal proportion of light drinkers and heavy drinkers in the population, the comparison of drinkers (light and heavy) and nondrinkers may results in null effect.…”
Section: Effect Of Alcohol Drinking On Erectile Dysfunction In Chinesmentioning
confidence: 99%
“…12 The relationship between alcohol drinking and ED remained inconsistent in earlier studies. 13,14 Only two studies examined such relationship among Chinese subjects, 15,16 but the results were also indefinite. Even alcohol drinking and smoking are concurrent habits for many subjects, the effect of alcohol intake on ED among smokers has been infrequently addressed.…”
Section: Introductionmentioning
confidence: 99%